2022
DOI: 10.3389/fpsyt.2022.792402
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mobile Games in the Management of Patients With Attention Deficit Hyperactive Disorder: A Scoping Review

Abstract: Attention deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorder associated with significant morbidity. Current treatment approaches consist of a mixture of pharmacological and psychological approaches. The emergence of digital technology, and mobile gaming applications, represents a promising novel method in potentially augmenting existing interventions for ADHD. In this review, we will map out the use of mobile gaming applications in the management of ADHD and evaluate the effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It is also very effective as a home treatment tool or learning material in the case of exceptional social circumstances, such as the isolation due to the COVID-19 pandemic. Existing studies indicate that providing digital treatment interventions through mobile devices can increase the access to treatment and reduce treatment costs, which, in turn, can help improve compliance [ 44 ]. NeuroWorld DTx research offers the advantage of improving the objectively measured inattentiveness of pediatric ADHD patients and increasing compliance through greater motivation and the active participation of children, including those refusing to participate in the study, or not giving up or missing out on participants.…”
Section: Discussionmentioning
confidence: 99%
“…It is also very effective as a home treatment tool or learning material in the case of exceptional social circumstances, such as the isolation due to the COVID-19 pandemic. Existing studies indicate that providing digital treatment interventions through mobile devices can increase the access to treatment and reduce treatment costs, which, in turn, can help improve compliance [ 44 ]. NeuroWorld DTx research offers the advantage of improving the objectively measured inattentiveness of pediatric ADHD patients and increasing compliance through greater motivation and the active participation of children, including those refusing to participate in the study, or not giving up or missing out on participants.…”
Section: Discussionmentioning
confidence: 99%
“…By providing a gamified environment for therapeutic exercises, these games increase the engagement and motivation of rehabilitation. Active engagement is facilitated by the immersive qualities of serious games, which enhances the efficacy of rehabilitation interventions (Bukovšek et al, 2020;Jiang et al, 2022;Cervantes et al, 2023). Concurrently with the development of serious games, the incorporation of reinforcement learning, a form of artificial intelligence (AI), enhances the capabilities of technological interventions in this field.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, regarding ADHD, there have been further studies examining the evidence base of existing games for individuals with ADHD and the potential of gamification for serious games targeting individuals with ADHD. Jiang et al [ 10 ] conducted a scoping review of the currently available mobile games on several databases, and they reported that most of the existing games were focused on managing individuals with symptoms and less so on symptoms and diagnosis. Although the studies have shown an improvement in the performance of the children across the interventions, these studies were limited in several aspects, such as the inclusion of a small sample size and lack of a control group for comparison, and these factors influence the overall effectiveness of the study [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al [ 10 ] conducted a scoping review of the currently available mobile games on several databases, and they reported that most of the existing games were focused on managing individuals with symptoms and less so on symptoms and diagnosis. Although the studies have shown an improvement in the performance of the children across the interventions, these studies were limited in several aspects, such as the inclusion of a small sample size and lack of a control group for comparison, and these factors influence the overall effectiveness of the study [ 10 ]. Nonetheless, the 19 studies highlighted the potential of considering a serious game approach when conceptualizing new interventions, and they also revealed that the most common techniques were that of having participants to respond to various cues, remembering details, or making association between different entities [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation